PERAN TENAGA KERJA WANITA DALAM USAHATANI HORTIKULTURA DI KELURAHAN WAILAN, TOMOHON UTARA, KOTA TOMOHON - Marlina ., Damatun; Ventje V. Rantung; Melsje Y. Memah (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine of women workers in the horticultural farm in the Village Wailan. The research was conducted in November 2016 to April 2017, from preparation to preparation of the report. The data used primary data and secondary data. This research was conducted with a purposive sampling technique, the number of samples taken by 30 respondents. The data were analyzed descriptively presented in table form. The results showed that the working hours of women at Harvest activity of 2.56 hours / day, planting 1.7 hours / day, tillage 1.66 hours / day, weeding 0.46 hours / day, nursery 0.4 hours / day , fertilization 0.26 hours / day and control of pests and diseases 0 hours / day.